Clinical, economic, and health‐related quality of life outcomes in patients with overweight or obesity in the United States: 2016-2018 - Joanna P. MacEwan; Kevin Chiu; Nadia N. Ahmad; Naomi Sacks; Shraddha Shinde; Jiat Ling Poon; Hong Kan (Wiley, 2024)
Abstract Objectives This study aimed to estimate clinical, economic (including productivity), and health‐related quality of life (HRQoL) outcomes and associated individual characteristics among adults with overweight (OW) or obesity in the United States. Methods This study included adult respondents with body mass index (BMI) ≥18.5 kg/m2 in the 2017-2018 National Health and Nutrition Examination Survey (NHANES) and 2016 Medical Expenditure Panel Survey. Respondents were classified according to BMI. Individual characteristics were described by BMI categories. Multivariable regression models estimated the association between BMI categories and outcomes, adjusting for individual characteristics. Results Nearly three‐quarters (73.7%) of NHANES participants were OW or obese. Relative to Normal weight (NW), respondents with Class 3 obesity had more obesity‐related complications (2.07 vs. 4.62, p < 0.001). Higher BMI was associated with significantly lower HRQoL, lower productivity, and higher healthcare expenditures as well as more frequent weight loss attempts in the previous 12 months. Weight loss surgery and prescription anti‐obesity medications (AOMs) were used only by a very small proportion of individuals. Despite frequent weight loss attempts, most respondents did not achieve clinically meaningful weight loss. Conclusions Adults with OW or obesity experienced worse clinical, economic and HRQoL outcomes than those with NW. Better use of evidence‐based obesity treatments, including prescription AOMs, should be considered to achieve more clinically meaningful weight reduction and improved outcomes in individuals with OW or obesity.